TOXICITY TEST OF GARLIC EXTRACT ON VERO CELLS IN VITRO - Pandu Rana Yudhisi; Debby Saputera; widodo widodo (FKG Unlam, 2019)
Background: Denture stomatitis is an inflammation that occurs in the mucosa covered by dentures that is often attributed to increased colonization of the yeast Candida albicans that predisposes bacterial infections. Denture Stomatitis can occur due to the lack of awareness in maintaining denture hygiene. One alternative natural ingredient to serve as denture cleanser is garlic extract. Several studies have shown that garlic extract, contains flavonoids, essential oils, tannins and, mostly, allicin, exerts antibacterial and antifungal properties. Purpose: To investigate whether garlic extract (Allium Sativum L) is toxic to Vero cells using the MTT assay method. Method: This study was a purely experimental study, conducted using posttest-only with control group design. The samples were divided into 8 groups, consisted of several concentrations of garlic extract, including 0.5%, 1%, 2.5%, 5%, 7.5%, 10%, 12.5% and 15%, and 2 control groups, including control media and cell control. The absorbance was read using ELISA reader and the cell viability was calculated. Result: The value of Inhibitory Concentration (IC50) of garlic extract on Vero cells was obtained from the spss probit test that resulted in a value of 18613.782 µg/mL. Conclusion: Garlic extract does not have a toxic effect on Vero cells as indicated by the IC50 value of >1000 μg/mL.